The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.31436/iiumej.v18i2.806
|View full text |Cite
|
Sign up to set email alerts
|

Study of Different Treatment Methods on Chicken Feather Biomass

Abstract: The chicken feathers (CFs)  consist of up to 10 % of total chicken dry mass and they have many potential industrial applications. CFs contains protein fibers named as keratin, which is an insoluble protein. Primary sanitization phases are complex because of the presence of lots of blood born microbes, pathogens and parasites in raw biomass. The extraction process of keratins from the unprocessed feathers is also a challenging task. Prior to the extraction cleaning/sanitization of feathers is a very necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The protein sample was stable until 200 °C, which confirms the thermal stability of hair proteins during our extraction process. A sharp weight loss occurred from 200 to 400 °C with a decreased range reaching up to 60%, probably due to the denaturation of protein structures. A significant weight loss was observed when the temperature was higher than 400 °C, with approximately 60% lost weight associated with protein decomposition around 500 °C, suggesting that the temperature applied in our extraction process would not break keratin peptide bonds …”
Section: Resultsmentioning
confidence: 96%
“…The protein sample was stable until 200 °C, which confirms the thermal stability of hair proteins during our extraction process. A sharp weight loss occurred from 200 to 400 °C with a decreased range reaching up to 60%, probably due to the denaturation of protein structures. A significant weight loss was observed when the temperature was higher than 400 °C, with approximately 60% lost weight associated with protein decomposition around 500 °C, suggesting that the temperature applied in our extraction process would not break keratin peptide bonds …”
Section: Resultsmentioning
confidence: 96%
“…It was observed that the absorption band assigned to the –OH groups of cellulose appears at ν 3350 cm −1 . Other cellulose-specific peaks were found at ν 2894, 1427, 1350, 870 and 655 cm −1 which are assigned to –CH stretching bands, (HCH, OCH) bending inside of plane vibration, –CH deformation vibration, (COC, CCO, CCH) deformation mode stretching vibrations, and C–OH banding out of plane; respectively 50 , 51 .
Figure 4 FTIR spectra of BC by HS medium (red) and that based on EDCFs medium (black) lines.
…”
Section: Resultsmentioning
confidence: 99%
“…The broad vibration band region between 3400 and 3250 cm –1 was attributed to the O–H and N–H stretching vibrations (Amide A). The bands that appeared in the range between 3000 and 2800 cm –1 were ascribed to C–H stretching bonds. ,, Amide I was mainly associated with CO stretching absorption in the range of 1700–1600 cm –1 . Amide II was associated with N–H bending and C–H stretching vibration with absorption at 1540–1520 cm –1 . , While the bands between 1300 and 1220 cm –1 are ascribed to the amide III band due to the combination of N–H bending and C–N stretching vibration. , The presence and position of these bands confirm the representative structure of the protein and indicate that the chemical structure of the proteins is retained after the extraction processes.…”
Section: Resultsmentioning
confidence: 96%
“…The bands that appeared in the range between 3000 and 2800 cm –1 were ascribed to C–H stretching bonds. 9 , 24 , 50 Amide I was mainly associated with C=O stretching absorption in the range of 1700–1600 cm –1 . 24 Amide II was associated with N–H bending and C–H stretching vibration with absorption at 1540–1520 cm –1 .…”
Section: Resultsmentioning
confidence: 99%